Elucidating performance failures in use of granular sludge for nutrient removal from domestic wastewater in a warm coastal climate region. Issue 15 (2nd July 2020) - Guimarães, Lorena B.; Wagner, Jamile; Akaboci, Tiago R. V.; Daudt, Gilberto C.; Nielsen, Per H.; van Loosdrecht, Mark C. M.; Weissbrodt, David G.; da Costa, Rejane H. R.
ABSTRACT: The effects of domestic wastewater and a coastal warm climate on granular sludge and biological nutrient removal were evaluated using a pilot-scale sequencing batch reactor (SBR). The reactor operation employed two different operational strategies (OS) based on up-flow feeding regimes, defined as fast (OS1, flow rate = 18.0 L min −1 and flow velocity = 22.0 m h −1 ) and slow (OS2, flow rate = 3.5 L min −1 and flow velocity = 4.3 m h −1 ). Under slow feeding, larger (OS1: 290 µm; OS2: 450 µm) and faster settling granules were obtained (OS1: 109; OS2: 74 mL g −1 TSS). The slow feeding regime was also advantageous for the hydrolysis of particulate organic matter (OS1: 1.3; OS2: 3.1 g CODtot g −1 VSS d −1 ) and for phosphorus removal (OS1: <33%; OS2: >97.5%). Neither strategy resulted in substantial biomass accumulation in the reactor (OS1: 0.7; OS2: 1.5 g VSS L −1 ), and high concentrations of nitrite were observed in the effluent (9–27 mg N O 2 − − N L −1 ). Ordinary heterotrophic organisms dominated the granular sludge developed under both feeding regimes (OS1: 30% of Thauera ; OS2: 56% of Comamonas ), while polyphosphate-accumulating organisms (PAOs) were only detected during OS2 (2.3–3.4% of total bacteria). A successful granular sludge process should be able to cope with high fluctuations in wastewater loads caused by rain events (82–182 mm month −1 in Florianopolis, Brazil). In order to achieve higher water quality, strategies identified for an efficient granular sludge SBR operation included (i) management of an anaerobic phase for PAO selection, and (ii) aeration control for successful nitrification/denitrification. GRAPHICAL ABSTRACT: